The biota of the Upper Cretaceous site of “Lo Hueco” (Cuenca, Spain) - Ortega, F.; Bardet, N.; Barroso-Barcenilla, F.; Callapez, P.M.; Cambra-Moo, O.; Daviero- Gómez, V.; Díez Díaz, V.; Domingo, L.; Elvira, A.; Escaso, F.; García-Oliva, M.; Gómez, B.; et al. (Journal of Iberian Geology, 2015)
The Late Cretaceous (Campanian-Maastrichtian) fossil site of Lo Hueco was recently discovered close to the village of Fuentes (Cuenca, Spain) during the cutting of a little hill for installation of the railway of the Madrid-Levante high-speed train. To date, it has yielded a rich collection of well-preserved Cretaceous macrofossils, including plants, invertebrates, and vertebrates. The recovered fossil assemblage is mainly composed of plants, molluscs (bivalves and gastropods), actinopterygians and teleosteans fishes, amphibians, panpleurodiran (bothremydids) and pancryptodiran turtles, squamate lizards, eusuchian crocodyliforms, rhabdodontid ornithopods, theropods (mainly dromaeosaurids), and titanosaur sauropods. This assemblage was deposited in a near-coast continental muddy floodplain crossed by distributary sandy channels, exposed intermittently to brackish or marine and freshwater flooding as well as to partial or total desiccation events. The Konzentrat-Lagerstatt of Lo Hueco constitutes a singular accumulation of fossils representing individuals of some particular lineages of continental tetrapods, especially titanosaurs, eusuchians and bothremydid turtles. In the case of the titanosaurs, the site has yielded multiple partial skeletons in anatomical connection or with a low dispersion of their skeletal elements. A combination of new taxa, new records of taxa previously known in the Iberian Peninsula, and relatively common taxa in the European record compose the Lo Hueco biota. The particular conditions of the fossil site of Lo Hueco and the preliminary results indicate that the analysis of the geological context, the floral and faunal content, and the taphonomical features of the site provide elements that will be especially useful for reassess the evolutionary history of some lineages of European Late Cretaceous reptiles.